Optimalisasi Tata Letak Gudang Menggunakan Metode Dedicated Storage Untuk Meminimasi Biaya Perpindahan Barang - Fajri, Fajri Indrawan Imam; Butarbutar, Florida; Hadiwijaya, Syarif; Assidiq, Muhammad Nurhasan (Universitas Muhammadiyah Sorong, 2025)
The high cost of moving goods in the P3WH1 warehouse of PT Astra Honda Motor is caused by a less than optimal warehouse layout. A layout that does not have good rules will certainly make it difficult for operators to organise items to be stored or retrieved. Because it will require inefficient time and distance travelled in retrieving and storing goods. This study aims to reduce the cost of moving goods through layout improvements with the dedicated Storage method. The methods used include analysing the current warehouse layout, redesigning the layout using the dedicated storage method, and simulating the cost of moving goods before and after improvement. The results showed that the new layout can reduce the cost of moving goods and improve the operational efficiency of the warehouse. Comparison of the results of the displacement distance of the layout before and after improvement is 3,156 m / month. While the comparison of the results of the calculation of material handling costs before and after the improvement is Rp3,828,274.56/year. The main conclusion of this research is that the application of the dedicated storage method is effective in minimising the cost of moving goods. The contribution of this research is to provide practical guidance for companies in designing warehouse layouts that are more efficient and reduce operational costs.